Investigation of the effect of print parameter on dimensional accuracy for fused deposition modelling (FDM) 3D printer - Nurul Najaa, Sharizal; Jaapar, Mohd Hamka; Khairul Fikri, Muhammad (Institution of Engineering and Technology, 2022)
This paper is to study on the effect of print parameters on dimensional accuracy using Fused Deposition Modelling (FDM) in three-dimensional (3D) printing. Generally, FDM is one of the most popular methods for manufacturing 3D printed parts due to its vast availability. Hence, the material chosen as a matter of study in this research is known as Polylactic acid (PLA). For this study, the nozzle diameter for all specimen is set constant at 0.4 mm. Thus, the method used to measure the printed sample is using Optical Video Measuring System.After understanding the progression of the dimensional accuracy, an optimization model was created which is by using the method of Taguchi with the aim to minimize the value of the optimum parameter combination that was dependent on printing parameters which is namely as extrusion speed, extrusion temperature and extrusion rate. The optimum parameters from this study are; printing speed is 50 mm/s, nozzle temperature is 220 °C and feed rate is l5 mm/s.